AB0073 BOSWELLIA SERRATA EXTRACT AND CURCUMIN INCREASE GDF15 PRODUCTION BY HUMAN PRIMARY OSTEOARTHRITIS CHONDROCYTES: A NEW MECHANISM OF ACTION. (2nd June 2020) - Sanchez, C.; Zappia, J.; Dierckxsens, Y.; Delcour, J. P.; Henrotin, Y.
Abstract : Background: Boswellia serrata extract (BSE) and curcumin are used to relief symptoms in osteoarthritis (OA). Objectives: This study aims to better understand the mode of action of these compounds on OA chondrocytes in vitro . Methods: Therapeutic plasmatic concentrations of the different components of BSE correspond to an in vitro range from 25 to 100 µg/ml of total BSE (100 µg/ml of BSE corresponds to 9.2 µM of 11-keto-β-boswellic acid (KBA), 5.2 µM of acetylKBA, 22 µM de αBA, 34 µM de βBA, 4.4 µM de acetylαBA and 13.2 acetyl βBA), and between 2 to 10 µM for bioavaibility-increased curcumin. BSE (5-100 µg/ml) and curcumin (0.04 to 4 µg/ml corresponding to 0.1 to 10 µM) were tested separately on primary chondrocytes from 3 OA patients. Lactate Deshydrogenase LDH, nitrite (NO2 ), interleukin (IL)-6 and Growth Differentiation Factor (GDF)15 were quantified in 72h-treated supernatant using enzyme activity, Griess reaction and ELISAs, respectively. Results: No mortality was observed at the tested concentrations. BSE and curcumin both decreased concentration-dependently NO2 and IL-6 production, and increased GDF15 production. For NO2 production, the decrease was observed from 0.2 µg/ml of curcumin and 10 µg/ml of BSE. For IL-6 production, the decrease was observed from 1 µg/ml for curcumin and 10 µg/ml for BSE. For GDF-15, the increase was observed from 2 µg/ml for curcumin and 50 µg/ml for BSE. Maximal effect was observed at 4 µg/ml for curcumin: -67% NO2 (p<0.0001), -71% IL-6 (p=0.0001) and +80% GDF15 (p<0.0001) and at 100 µg/ml for BSE: -40% NO2 (p=0.0003), -70% IL-6 (p=0.0003) and +73% for GDF15 (p=0.0017). Conclusion: At therapeutic plasmatic concentrations, BSE and curcumin decreased the production of NO2 and IL-6, two inflammatory mediators. Furthermore, BSE and curcumin enhanced GDF-15 production, an anti-inflammatory growth factor. GDF15 was first identified as Macrophage inhibitory cytokine-1 or NSAID-activated gene-1 (by a prostanoid-independent manner), and is known as a regulator of inflammatory, cell repair and apoptosis pathways. GDF-15 has pro-apoptotic and anti-tumorigenic activity in vitro and in vivo. It could represent a new pathway explaining the beneficial effects of BSE and the curcumin on synovium inflammation and cartilage degradation. Disclosure of Interests: christelle sanchez: None declared, Jérémie Zappia: None declared, Yvan Dierckxsens Shareholder of: Tilman SA, Employee of: Tilman SA, Jean-Pierre Delcour: None declared, Yves Henrotin Grant/research support from: HEEL, TILMAN